An Investigation into the Association Between Dopamine Receptor D1 Multilocus Genetic Variation, Multiparametric Magnetic Resonance Imaging, and Antidepressant Treatment. Issue 1 (6th December 2021) - Sun, Yurong; Wang, Xinyi; Tian, Shui; Chen, Zhilu; Wang, Huan; Xue, Li; Yan, Rui; Yao, Zhijian; Lu, Qing
Abstract : Background: Combining genetic variants with neuroimaging phenotypes may facilitate understanding of the biological mechanisms for the etiology and pharmacology of antidepressant treatment of major depressive disorder (MDD). Purpose: To explore the latent pathway of dopamine gene–hierarchical brain network–antidepressant treatment. Study Type: Retrospective. Population: One hundred and sixty‐eight MDD inpatients divided into responders (N = 98) or nonresponders (N = 70) based on the treatment outcome of antidepressant. Field Strength/Sequence: Diffusion tensors imaging and resting‐state functional magnetic resonance imaging at 3.0T using echo‐planar sequence. Assessment: Four genetic variations of the dopamine receptor D1 ( DRD1 ) were genotyped. Strengths of rich‐club, feeder, and local connections were calculated based on the rich‐club organizations of structural and functional brain networks at baseline and following 4 weeks of selective serotonin reuptake inhibitor (SSRI) therapy. Statistical Tests: Logistic and linear regressions were used to analyze the impact of DRD1 multilocus genetic profile score on the treatment response of SSRI, and their associations with strengths of rich‐club, feeder, and local connections. Mediation models were developed to explore the mediation role of rich‐club organizations on the relationship between DRD1 and SSRI therapy response. A P value <0.05 was considered to be statistically significant. Results: Multiple genetic variations of DRD1 were significantly related to the strengths of feeder connections both in structural and functional networks, and to the treatment response of SSRI. Furthermore, the strength of the structural feeder connection significantly modulated the effect of DRD1 variants on SSRI treatment outcome. Data Conclusion: DRD1 displayed close connections both with SSRI treatment outcome and rich‐club organizations of structural and functional data. Moreover, structural feeder connection played a mediating role in the relationship between DRD1 and antidepressant therapy. Level of Evidence: 3 Technical Efficacy Stage: 4